2017
DOI: 10.1002/asia.201700353
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Functionalized Ynamides with Tetracyanoethylene: Scope, Limitations and Optoelectronic Properties of the Adducts

Abstract: The reactivity of functionalized ynamides and arylynamines with tetracyanoethylene at room temperature was evaluated. In most cases, the corresponding 1,1,4,4-tetracyanobutadienes (TCBDs) were obtained in good to excellent yields through a [2+2]-cycloaddition/[2+2]-retro-electrocyclization sequence. The influence of diverse functional groups on the yield of the reaction was investigated, in particular concerning multiple ynamides. These TCBDs were characterized by various spectroscopic techniques and electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Compound 3 a was then subjected to Hsung conditions to form ynamide 4 a in a modest 26 % yield (unoptimized due to the very low solubility of 3 a ). Reaction of 4 a with TCNE through [2+2] cycloaddition followed by retro‐electrocyclization, (CA‐RE sequence) finally afforded the target carbo[4]helicene‐TCBD derivative 1 a in 99 % yield. The product was fully characterized; its 1 H NMR spectrum featured the typical signals for the [4]helicenic core (see the Supporting Information), such as two typical downfield signals of the shielded H 11 and H 12 (see Figure ) at δ =9.33 and 8.96 ppm, respectively; its 13 C NMR spectrum showed the characteristic peaks of the four cyano groups resonating between δ =110 and 113 ppm, unambiguously indicating the presence of the TCBD moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 a was then subjected to Hsung conditions to form ynamide 4 a in a modest 26 % yield (unoptimized due to the very low solubility of 3 a ). Reaction of 4 a with TCNE through [2+2] cycloaddition followed by retro‐electrocyclization, (CA‐RE sequence) finally afforded the target carbo[4]helicene‐TCBD derivative 1 a in 99 % yield. The product was fully characterized; its 1 H NMR spectrum featured the typical signals for the [4]helicenic core (see the Supporting Information), such as two typical downfield signals of the shielded H 11 and H 12 (see Figure ) at δ =9.33 and 8.96 ppm, respectively; its 13 C NMR spectrum showed the characteristic peaks of the four cyano groups resonating between δ =110 and 113 ppm, unambiguously indicating the presence of the TCBD moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The identity of these donors varies, and the yield of the reaction strongly depends on their nature. Some years ago, some of us reported the synthesis of TCBDs from ynamides, which served as electron‐rich alkynes ,. Their reduction potentials were among the lowest hitherto reported for TCBDs, allowing us to envisage promising applications by tuning the properties of extended π‐systems.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Recently,a ctivation by donors featuring nitrogen atoms directly attached to the alkyne was found to be quite effective. [32] Apart from the purely organic systems,arepresentative organometallic substance,f errocene,h as often been employed as ad onor substituent. [31] They ields of the triazene derivatives were good, whereas the alkynes activated by ynamide units afforded the TCBDs nearly quantitatively (92-98 %; Table 1, entry 16).…”
Section: Electron Donors Activating the Alkyne Componentmentioning
confidence: 99%
“…[31] They ields of the triazene derivatives were good, whereas the alkynes activated by ynamide units afforded the TCBDs nearly quantitatively (92-98 %; Table 1, entry 16). [32] Apart from the purely organic systems,arepresentative organometallic substance,f errocene,h as often been employed as ad onor substituent. Mochida et al optimized the conditions and reported aC A-RE reaction of ethynylferrocene with TCNE in yields up to 99 % ( Table 1, entry 17).…”
Section: Electron Donors Activating the Alkyne Componentmentioning
confidence: 99%
“…The same kind of results was observed when reacting compound 11d with TCNE. It confirms that Nalkylynamines, contrary to N-arylynamines, [22,23] are not able to afford TCBDs by reaction with TCNE in these conditions.…”
mentioning
confidence: 63%